The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1980
DOI: 10.1038/288373a0
|View full text |Cite
|
Sign up to set email alerts
|

The obligatory role of endothelial cells in the relaxation of arterial smooth muscle by acetylcholine

Abstract: Despite its very potent vasodilating action in vivo, acetylcholine (ACh) does not always produce relaxation of isolated preparations of blood vessels in vitro. For example, in the helical strip of the rabbit descending thoracic aorta, the only reported response to ACh has been graded contractions, occurring at concentrations above 0.1 muM and mediated by muscarinic receptors. Recently, we observed that in a ring preparation from the rabbit thoracic aorta, ACh produced marked relaxation at concentrations lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

91
4,568
15
206

Year Published

1987
1987
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10,911 publications
(4,945 citation statements)
references
References 8 publications
91
4,568
15
206
Order By: Relevance
“…The endothelium regulates the contractility of the underlying vascular smooth muscle cells by releasing a number of factors, the most important of which are the nitric oxide (NO) and endothelium derived hyperpolarizing factor (EDHF). These two factors play a major role in the controlling of vascular homeostasis [4649]. Endothelial NO-release is related to an activation of the endothelial nitric oxide synthase (eNOS) and can be stimulated by various agonists.…”
Section: Cardiovascular Effectmentioning
confidence: 99%
“…The endothelium regulates the contractility of the underlying vascular smooth muscle cells by releasing a number of factors, the most important of which are the nitric oxide (NO) and endothelium derived hyperpolarizing factor (EDHF). These two factors play a major role in the controlling of vascular homeostasis [4649]. Endothelial NO-release is related to an activation of the endothelial nitric oxide synthase (eNOS) and can be stimulated by various agonists.…”
Section: Cardiovascular Effectmentioning
confidence: 99%
“…It would take another century until 1998 that a Nobel prize was awarded for the discovery of NO's role in endothelial function. Robert F. Furchgott and colleagues [8] had observed that acetylcholine dilated blood vessels only if the endothelium was intact. He and Louis J. Ignarro identified the endothelium-derived relaxation factor as identical to .…”
Section: Introductionmentioning
confidence: 99%
“…It has been known that Ach induces vasodila tion by releasing endothelium-derived relaxing factor (EDFR), since the concept was introduced by Furch gott. 24 Gryglewski et al25 demonstrated that EDRF is protected from breakdown by superoxide dismutase and superoxide radicals contribute significantly to the instability of EDRF. Recently Nakazono et aP6 indic ated that superoxide radicals in and around vascular endothelial cells play critical roles in the pathogenesis of hypertension in the spontaneously hypertensive rat.…”
Section: Discussionmentioning
confidence: 99%